Réinscrire les mobilités quotidiennes dans leurs contextes. Une typologie des journées de travail des navetteur⋅ses en France - Maxime Guinepain (Cybergeo)
As energy costs rise and the need for a global ecological transition becomes increasingly pressing, daily commuting has emerged as a critical concern. To better understand the implications of these changes, this article analyses commuting practices by re-situating them within the broader framework of the workday in which they take place. Building on a substantial body of research that has examined travel distances across various contexts, it also brings attention to often overlooked dimensions such as presence periods, activity patterns, and scheduling.This paper draws on 67 mobility interviews conducted in France between 2008 and 2019. This rich corpus allows for the development of a typology of workdays, constructed through factor analysis and k-means clustering. While revisiting well-established findings—such as the link between the population density of residential areas and commuting distances—it also reveals that daily mobility patterns vary according to occupation and gender, reflecting broader social hierarchies. The study further suggests that certain forms of daily organisation carry distinctive social value.These results highlight the need to give greater importance to the temporal analysis of daily mobility, as it offers insights into the effects of congestion and supports a broader definition of accessibility that takes socio-spatial inequalities into account. The alignment between privileged social positions and extensive mobility also raises critical questions, particularly as moderation and the restriction of these highly valued practices have become increasingly promoted in environmental policies